2005
DOI: 10.1007/s10339-005-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of temporal sequencing of motor regulation guided by an auditory cue—a comparison with visual guidance

Abstract: The neuronal system to process and transfer auditory information to the higher motor areas was investigated using fMRI. Two different types of internal modulation of auditory pacing (1 Hz) were combined to design a 2x2 condition experiment, and the activation was compared with that under a visual guidance. The bilateral anterior portion of the BA22 (ant-BA22) and the left BA41/42 were more extensively activated by the combined modulation condition under the auditory cue than that under the visual cue. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Therefore, in order to verify the robustness of the functional connectivity patterns obtained in this study, further substantiation is necessary (preferably utilizing wide range of methodologies). Additionally, it is likely that other regions such as the basal ganglia, visual cortex and the cerebellum may also prove to be important candidates concerning functional connectivity for bimanual finger coordination (e.g., Battaglia-Mayer et al, 2001; Rizzolatti and Luppino, 2001; Nakai et al, 2003, 2005; Rowe et al, 2006; Grefkes et al, 2008; Hanakawa et al, 2008; Filimon, 2010; Leech et al, 2012; Zilverstand et al, 2014). Specifically, Aramaki et al's (2011) fMRI study on the phase-transition in young adults highlighted a potential role for the anterior putamen as a predictor of future instability for the anti-phase finger tapping.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to verify the robustness of the functional connectivity patterns obtained in this study, further substantiation is necessary (preferably utilizing wide range of methodologies). Additionally, it is likely that other regions such as the basal ganglia, visual cortex and the cerebellum may also prove to be important candidates concerning functional connectivity for bimanual finger coordination (e.g., Battaglia-Mayer et al, 2001; Rizzolatti and Luppino, 2001; Nakai et al, 2003, 2005; Rowe et al, 2006; Grefkes et al, 2008; Hanakawa et al, 2008; Filimon, 2010; Leech et al, 2012; Zilverstand et al, 2014). Specifically, Aramaki et al's (2011) fMRI study on the phase-transition in young adults highlighted a potential role for the anterior putamen as a predictor of future instability for the anti-phase finger tapping.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Within these areas, the primary motor area (M1) serves to execute the bimanual finger movements (Schieber and Poliakov, 1998; Aoki et al, 2003, 2005; Scott, 2003, 2008; Koeneke et al, 2004; Jaillard et al, 2005; Gao et al, 2008; Madden et al, 2010), while both the supplementary motor area (SMA) and the premotor area (PMA) are considered to be interactively responsible for planning the preparation of the motor actions involved (Deiber et al, 1996; Nakai et al, 2003; Solodkin et al, 2004; Simmonds et al, 2008; Rowe and Siebner, 2012; Hétu et al, 2013). Furthermore, the primary somatosensory area (S1) and superior parietal lobule (SPL) play notable roles especially in higher-order visuo-motor coordination (Debaere et al, 2004; Stoeckel et al, 2004; Nakai et al, 2005; Stanley and Miall, 2007; Granek et al, 2012; Baumgartner et al, 2013). Lesion studies also support the importance of these regions regarding different aspects of bimanual coordination (Tanaka et al, 1996; Stančák et al, 2003; Jaillard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, activations observed in left temporal/temporo‐parietal regions have not been restricted to language comprehension tasks or even to the domain of language (e.g., Bischoff‐Grethe et al. 2000; Saxe and Kanwisher 2003; Nakai et al. 2005).…”
Section: The Neural Basis Of Language: Where Things Standmentioning
confidence: 99%
“…Second, neuroimaging data have revealed activations in left frontal regions for a wide variety of language tasks (many of these not related to language production (e.g., Stromswold et al 1996;Dapretto and Bookheimer 1999;Ben-Shahar et al 2003)), as well as for tasks in other cognitive domains (e.g., Paulesu et al 1993;Braver et al 1997;Gabrieli et al 1998;Binkofski et al 2000;Duncan and Owen 2000;Fincham et al 2002;Hamzei et al 2003;Levitin and Menon 2003;Buccino et al 2004;Nishitani et al 2005;Koechlin and Jubault 2006;Tettamanti and Weniger 2006;Novais-Santos et al 2007). Similarly, activations observed in left temporal/ temporo-parietal regions have not been restricted to language comprehension tasks or even to the domain of language (e.g., Bischoff-Grethe et al 2000;Saxe and Kanwisher 2003;Nakai et al 2005). Thus, Broca's area doesn't appear to be specific to language production.…”
Section: The Neural Basis Of Language: Where Things Standmentioning
confidence: 99%
“…The left temporal lobe is known to handle the timing of complex movements with auditory cues (Nakai et al, 2005). Previous fMRI studies revealed that the superior temporal sulcus and posterior middle temporal gyrus of the left hemisphere are more selective to body actions and actions performed on other objects, respectively (Jellema and Perrett, 2006; Assmus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%